The Czech - Slovak Relationships in the School Policy in the Years Of 1918-1939 and the Personnel Issue - Jarmila Zacharova (Communications - Scientific letters of the University of Zilina, 2014)
Czech-Slovak relations are an important component in the history of our nations. In the historical context they were developed actively in the 1920´s. The relations at these levels were mutually influenced and brought about several positive elements to the national heritage. As a consequence of the formation of the Czechoslovak Republic in 1918, there was a thorough spiritual and cultural renewal of the Slovak nation, which included the creation of a network of schools of all grades. The process of its building was not straightforward. It was connected with many obstacles and problems that demanded strategic and operative solutions. This article deals with the reconstruction of Czecho-Slovak relations in school politics in the years 1918-1939 in terms of personnel issues.